Afghan Women: Beyond Binaries. (March 2017) - Saba, Sahar; Sulehria, Farooq
In the mainstream narratives on the Afghan conflict, primacy is assigned to a binary of 'Mujahedeen' and People's Democratic Party of Afghanistan (PDPA) regime. The struggle of organisations, beyond this binary, such as the Revolutionary Association of the Women of Afghanistan (RAWA) against and during the communist rule, belies these narratives. Consequently, this article argues that women's liberation is not possible when a state/society is run by an autocratic regime denying democratic freedoms in general. This is equally true about present-day Afghanistan despite the staging of a mainstream intellectual/political spectacle to show that Afghan women were rescued by the USA. In the case of PDPA, we argue that through the harsh measures to subdue the opposition, the 'communist' regime introduced policies with huge consequences for women. Regarding the post-9/11 regime, we flag up its ideologically anti-women character. Therefore, we conclude that women's liberation cannot be achieved under foreign occupations.